Nonmaleficence pada Pasien Neonatal dengan Hiperbilirubinemia yang Menjalani Fototerapi: Analisa Konsep - Setyaningsih, Wahyu; Awaludin, Sidik (JURNAL KEPERAWATAN MERSI, 2024)
Background: The clinical ethical issue of nonmaleficence is not causing harm to patients. The principle of nonmaleficence requires that every medical action be weighed against all benefits, risks, and consequences. This principle reminds practitioners that the benefits of medical action should always be weighed against all risks and consequences. Objective: The concept analysis aimed to explore the nonmaleficence in neonatal hyperbilirubinemia patient undergoing phototherapy. Methods: Walker and Avants's method for concept analysis is used in this paper. This paper deï¬nes the attributes using the eight-step Walker and Avantâ€™s process of concept analysis method, such as the main objectives of the concept analysis process are to identify the attributes and provide researchers with a precise deï¬nition of the concept. Therefore, this analysis can provide a conceptualized deï¬nition of hyperbilirubinemia, phototherapy and nonmaleficence. The search method performing a literature searching PUBMED, Science Direct, ProQuest, and Google Scholar databases using the keywords hyperbilirubinemia, phototherapy, and nonmaleficence as key word and title. Published materials conducted from 2000 to 2023 in English or Indonesian. Â Results: The concept analysis showed that health workers in providing health care efforts must always be with the intention of helping patients overcome their health problems. Nursesâ€™ actions must be in accordance with procedures so that there are no errors or negligence that can harm patient and families so that they can provide maximum benefits and minimal risk. Conclusion: Nurse using ethical concept of nonmaleficence tried to explanation to mothers and family members in non-medical language.